Pengaruh Beban Kerja Terhadap Kinerja Karyawan Pada PT. Bank Rakyat Indonesia (Persero) Tbk. Kantor Cabang Tolitoli - Julistyono Widodo; Widiyawan Widiyawan (Fakultas Ekonomi Universitas Indonesia Timur, 2021)
This study aims to determine whether there is an effect of workload on employee performance. This research was conducted at PT. Bank Rakyat Indonesia (Persero) Tbk. Tolitoli Branch Office, Data collection methods are observation, interview, and questionnaire (questionnaire). The population in this study were some of the employees in the front liner and the marketing department, amounting to 44 people, the sampling technique used was conditional sampling or purposive sampling. The analytical method used is instrument test and hypothesis testing. Based on the results of the study, it can be concluded that workload affects employee performance at PT. Bank Rakyat Indonesia (Persero) Tbk. Tolitoli Branch Office as evidenced by the t-test results obtained t count 3.395 is greater than the t table is 2.018 which means that the workload affects employee performance. After testing the hypothesis, it is known that the results of the Pearson product-moment correlation analysis obtained a correlation coefficient of 0.464 or 46.4%. This shows that there is a positive relationship between workload variables and employee performance. The results of the analysis of the coefficient of determination R^2 or R Square obtained are 0.215 or 21.5%. This shows that employee performance is influenced by workload by 21.5% and 78.5% is influenced by other variables not examined in this study.